Sosialisasi Digital Marketing dan Pendampingan Pembuatan Website Penjualan pada Aplikasi Maxim untuk Pelaku UMKM Desa Kalisalam - Anjarwati, Ani; Hariyanto, Budi; Hermanto; Fitriana, Arum; Nasirruddin, Muhammad; Lusiana; Hasanah, Uswatul; Puspita, Devi; Putri, Siti Julaiha Ananda (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
In improving the products of the “Usaha Mikro Kecil Menengah (UMKM) in society 5.0, the use of social media is very important. One digital marketing solution that can be utilized by UMKM in Kalisalam Village is the Maxim expedition service. The aim of this research is to educate UMKM players regarding the importance of digital marketing and the application of creating sales websites on the Maxim application. The subjects of service are UMKM in Kalisalam Village, totaling 15 MSME. The method used is qualitative descriptive so that the results obtained are an introduction to digital marketing for UMKM players in Kalisalam Village starting from data collection on UMKM in Kalisalam Village, the process of implementing socialization and procedures for creating a sales website on the Maxim application.